Effect of continuous and intermittent electric current on lignin wastewater treatment and microbial community structure in electro-microbial system - Lulu Zhang (Nature Portfolio, 2019)
Abstract In this study, complex structured soluble lignin wastewater was treated by electro-microbial system (EMS) using different direct current (DC) application modes (CR (continuous ON), IR12h (12 h-ON/12 h-OFF) and IR2h (2 h-ON/2 h-OFF)), and physiological characteristics and microbial communities were investigated. Results showed that CR, IR12h and IR2h had higher lignin removals, which were almost two times that of the control reactor (R0′, no current), and IR2h performed best and stably. Furthermore, IR2h exhibited the lowest ohmic resistance (Rs) of electrode biofilms, which could be explained by its higher abundance of electroactive bacteria. In the activated sludge of EMS, the concentration of dehydrogenase activity (DHA) and electronic transport system (ETS) in IR2h were the highest (1.48 and 1.28 times of R0′), which contributed to its high content of adenosine triphosphate (ATP). The viability of activated sludge was not affected by different DC application modes. Phospholipid fatty acids (PLFA) analysis indicated that IR2h had the maximum content of C15:1 anteiso A, C16:0 and C18:0; CR increased the content of C15:0 anteiso and decreased the content of saturated fatty acids. Genus-level results revealed that lignin-degrading bacteria, Pseudoxanthomonas and Mycobacterium, could be enriched in IR2h and CR, respectively.